2010
DOI: 10.1021/jp100519q
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Synthesis of Bifunctional TiO2Catalysts and Their Photocatalytic Activity

Abstract: In this paper, we have investigated in detail the preparation of anatase TiO 2 catalysts by the controlled thermal decomposition of ammonium titanyl sulfate ((NH 4 ) 2 TiO(SO 4 ) 2 ) and their catalytic activity. The structures of anatase TiO 2 catalysts have been characterized by powder X-ray diffraction, N 2 adsorption-desorption isotherms, diffuse reflectance UV-vis spectroscopy, infrared spectroscopy, X-ray photoemission spectroscopy, NH 3 temperature-programmed desorption, and solid-state MAS NMR spectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 48 publications
3
33
0
Order By: Relevance
“…The O 1s XPS line of the SO 4 2À /ZrO 2 sample shows two signals centered at 531.6 (denoted O 1s (1)) and 532.6 eV (denoted O 1s(2)), respectively, originating from oxygen species in the ZrÀOÀZr and ZrÀOÀS bonds, respectively. [25] After the introduction of ethane-or phenylene-bridged organosilica fragments into the framework of SO 4 2À /ZrO 2 , the binding energies of O 1s (1) …”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…The O 1s XPS line of the SO 4 2À /ZrO 2 sample shows two signals centered at 531.6 (denoted O 1s (1)) and 532.6 eV (denoted O 1s(2)), respectively, originating from oxygen species in the ZrÀOÀZr and ZrÀOÀS bonds, respectively. [25] After the introduction of ethane-or phenylene-bridged organosilica fragments into the framework of SO 4 2À /ZrO 2 , the binding energies of O 1s (1) …”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…It had been reported by Fujishima et al [2] that TiO 2 semiconductor particles can be used as a photocatalyst for decomposition of water to oxygen and hydrogen. Since then, light-assisted cleavage of water on the surface of semiconductor particles to produce oxygen and hydrogen has been of continued interest [3][4][5][6][7]. In a couple of very recent reviews [3,4], the prospects for visible light-driven hydrogen generation over semiconductor photocatalysts in the presence of a sacrificial electron donor (SED) have been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Hartmann et al showed the effectiveness of sol-gel derived mp-TiO2 in the water splitting reaction, but its large bandgap limits visible light absorption [229]. To improve hydrogen production from water splitting using visible light, non-metal elements have been doped into mp-TiO2 [33,152,181,190,191,230]. First, Sreethawong et al prepared N-mp-TiO2 and assemblies of TiO2 nanocrystals [190].…”
Section: Water Splittingmentioning
confidence: 99%
“…An increase in Pt loading of more than 1.3 wt % decreased the hydrogen production due to increased Pt agglomeration, excessive coverage of the titania surface by the Pt nanoparticles, and an increased probability of charge recombination by the excess electrons on the Pt surface. Fang et al also showed the efficacy of Pt loading in N/S-mp-TiO 2 in water splitting [230]. The co-doped samples were prepared by controlled thermal decomposition of a single source, ammonium titanyl sulfate ((NH 4 ) 2 TiO(SO 4 ) 2 ).…”
Section: Water Splittingmentioning
confidence: 99%